2005
DOI: 10.1111/j.1365-2672.2005.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

EnterotoxigenicStaphylococcus aureusin bulk milk in Norway

Abstract: Aims: To investigate the presence of enterotoxigenic Staphylococcus aureus in bulk milk and in a selection of raw milk products. Methods and results: Samples of bovine (n ¼ 220) and caprine (n ¼ 213) bulk milk, and raw milk products (n ¼ 82) were analysed for S. aureus. Isolates were tested for staphylococcal enterotoxin (SE) production (SEA-SED) by reversed passive latex agglutination and for SE genes (sea-see, seg-sej) by multiplex PCR. Staphylococcus aureus was detected in 165 (75%) bovine and 205 (96AE2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
104
7
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 43 publications
31
104
7
12
Order By: Relevance
“…Similar to our results, S. aureus was detected in 24% of the raw OM samples collected from Epirus, Greece (Fotou et al 2011), whereas all milk samples collected from 21 sheep farms from the regions of Xanthi and Evros were positive for S. aureus . The data regarding the prevalence of S. aureus in CM and OM from other countries are also quite variable (Mørk et al 2003;Jørgensen et al 2005;de Garnica et al 2013;Spanu et al 2013;Cortimiglia et al 2015). Although differences in the sensitivity and specificity of the protocols used for bacterial isolation may have contributed to these variant results, the different husbandry practices applied in different countries may at least partly account for the aforementioned differences in prevalence estimates.…”
Section: Antibiotic Susceptibility Of S Aureus Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, S. aureus was detected in 24% of the raw OM samples collected from Epirus, Greece (Fotou et al 2011), whereas all milk samples collected from 21 sheep farms from the regions of Xanthi and Evros were positive for S. aureus . The data regarding the prevalence of S. aureus in CM and OM from other countries are also quite variable (Mørk et al 2003;Jørgensen et al 2005;de Garnica et al 2013;Spanu et al 2013;Cortimiglia et al 2015). Although differences in the sensitivity and specificity of the protocols used for bacterial isolation may have contributed to these variant results, the different husbandry practices applied in different countries may at least partly account for the aforementioned differences in prevalence estimates.…”
Section: Antibiotic Susceptibility Of S Aureus Isolatesmentioning
confidence: 99%
“…aureus appears to be isolated at high frequencies from raw small ruminants' milk, and studies conducted in various countries have shown that S. aureus isolates from caprine milk (CM) and ovine milk (OM) frequently produce SEs or harbor genes encoding for their synthesis (Jørgensen et al 2005;Morandi et al 2007). In addition, AR and MRSA S. aureus strains have been isolated from both bovine and small ruminants' milk in various countries, as summarized in the review of Pexara et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…(2000) que, utilizando à mesma técnica de OSP, avaliaram 127 amostras de estafilococos isolados de leite de animais com mastite e encontraram, em torno de 3% (4) com capacidade de produção de EEA. Outros autores, utilizando-se de técnicas como a aglutinação em látex e microslide para pesquisa de EEA em amostras de leite encontraram culturas de estafilococos produtoras de pouca quantidade de EEA e culturas não produtoras isoladamente desta toxina (JORGENSEN et al, 2005;CENCI-GOGA et al, 2003;OMBUI;ARIMI;KAYIHURA, 1992;HILL, 1983) O fato de até hoje os ECN serem pouco relacionados às intoxicações, não quer dizer que isso não possa vir a acontecer, uma vez que são vários os estudos relatando sua capacidade de produzir enterotoxina, principalmente "in vitro". Seria recomendável o estudo de capacidade enterotoxigênica em um número maior de ECN isolados de leite cru, bem como inoculações em leite para verificar a produção da toxina no alimento.…”
Section: Resultsunclassified
“…Atualmente são descritas em torno de dezoito enterotoxinas estafilocócicas sorologicamente distintas: EEA, EEB, EEC1, EEC2, EEC3, EED e EEG a EER e EEU (JORGENSEN et al, 2005).…”
Section: Introductionunclassified
“…[10] Indeed, milk is a good substrate for S. aureus growth, and dairy products are a known source of contamination. [11,12] S. aureus contamination can occur through the presence of S. aureus in the raw milk itself or during handling and processing of the milk. [13] Although pasteurization kills S. aureus cells, thermostable SEs generally retain their biological activity.…”
Section: Introductionmentioning
confidence: 99%